2009
DOI: 10.1111/j.1399-0004.2008.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple granular cell tumors are an associated feature of LEOPARD syndrome caused by mutation in PTPN11

Abstract: We report a patient with a clinical and molecular diagnosis of LEOPARD syndrome (LS) associated with multiple granular cell tumors (MGCT). Bidirectional sequencing of exons 7, 12, and 13 of the PTPN11 gene revealed the T468M missense mutation in exon 12. This mutation has been previously reported in patients with LS. To our knowledge, this is the first report of MGCT associated with molecularly characterized LS and provides the first molecular evidence linking granular cell tumors (GCT) to the Ras/mitogen-acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 39 publications
1
36
0
4
Order By: Relevance
“…Although acute lymphoblastic leukemia [Laux et al, 2008], acute myeloid leukemia [Uçar et al, 2006] and multiple granular cell tumor [Schrader et al, 2009] have been reported in patients with LS and PTPN11 mutation, the association is inconclusive [Kratz et al, 2011]. In fact, single case reports in the literature or translating the knowledge gathered in NS to LS patients do not reliably document an increased risk of malignancy in LS patients.…”
Section: Tumorsmentioning
confidence: 90%
“…Although acute lymphoblastic leukemia [Laux et al, 2008], acute myeloid leukemia [Uçar et al, 2006] and multiple granular cell tumor [Schrader et al, 2009] have been reported in patients with LS and PTPN11 mutation, the association is inconclusive [Kratz et al, 2011]. In fact, single case reports in the literature or translating the knowledge gathered in NS to LS patients do not reliably document an increased risk of malignancy in LS patients.…”
Section: Tumorsmentioning
confidence: 90%
“…Due to the rarity of malignant cases associated with LS, the association is inconclusive. However, acute lymphoblastic leukemia 15 , acute myeloid leukemia 16 , and multiple granular cell tumor 17 associated with LS with mutation in PTPN11 gene have been reported. Although predisposition of malignancy in LS remains debatable, LS patients with PTPN11 mutations should be closely monitored for malignancy, particularly during their childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Familial cases of multiple lesions have been reported, thus raising the possibility that some patients may have a genetic disposition towards this condition. Of the rare familial involvements [4,9,24], none has been reported in the vulva. To our knowledge, this is the first reported case of GCT of the vulva in the same family.…”
Section: Discussionmentioning
confidence: 99%
“…They were first described by Virchow and Weber in 1854 and again in 1926 by Abrikossoff, who designated them as ‘granular cell myoblastomas’ to convey his impression of their muscular origin. Recently, Schrader et al [4] hypothesized a link between Ras/MAP kinase pathway and multiple GCTs.…”
Section: Introductionmentioning
confidence: 99%